Amitriptyline removal using palygorskite clay. (July 2016) - Tsai, Yo-Lin; Chang, Po-Hsiang; Gao, Zong-You; Xu, Xiao-Yuan; Chen, Yan-Hsin; Wang, Zheng-Hong; Chen, Xin-Yu; Yang, Zheng-Ying; Wang, Tzu-Hao; Jean, Jiin-Shuh; Li, Zhaohui; Jiang, Wei-Teh
Abstract: With the increased detections of commonly used pharmaceuticals in surface water and wastewater, extensive attentions were paid recently to the fate and transport of these pharmaceuticals in the environment. Amitriptyline (AMI) is a tricyclic antidepressant widely applied to treat patients with anxiety and depression. In this study, the removal of AMI with palygorskite clay (PFl-1) was investigated under different physico-chemical conditions and supplemented by instrumental analyses. The uptake of AMI on PFl-1 was well fitted by the Langmuir isotherm with an adsorption capacity of 0.168 mmol g −1 at pH 6–7. The AMI uptake was fast and reached equilibrium in 15 min. The X-ray diffraction patterns showed no shift of the (110) peak position of palygorskite after AMI uptake. However, the (001) peak position of the minor component smectite (about 10%) shifted to lower angle as the amounts of AMI input increased. These results suggested surface uptake of AMI on palygorskite and interlayer uptake of AMI in smectite. As smectite is a common component of palygorskite clays, its role in assessing the properties and performances of palygorskite clays for the uptake and removal of contaminants should not be neglected. Overall, the high affinity of AMI for PFl-1 and strong retention of AMI on PFl-1 suggested that it could be a good adsorbent to remove AMI from wastewater. Palygorskite clays can also be a sink for many cationic pharmaceuticals in the environmental of the arid regions. Highlights: Palygorskite (PFl-1) is effective for the removal of amitriptyline (AMI). Uptake of AMI on PFl-1 is restricted to the external surfaces with fast rate. Cation exchange was the dominant mechanism for AMI uptake on PFl-1. Minor component smectite in PFl-1 contributed significantly to AMI uptake.